Effect of age and plant spacing on the energy properties of black wattle - Eloy, Elder; Silva, Dimas Agostinho da; Caron, Braulio Otomar; Trevisan, Rômulo; Balbinot, Rafaelo (Comunicata Scientiae, 2018)
The aim of this study was to determine the effect on the energy properties of different biomass components of Acacia mearnsii De Wild distributed in different plant spacings: 2.0x1.0 m, 2.0x1.5 m, 3.0x1.0 m and 3.0x1.5 m, in the 1st, 3rd and 5th years after planting. The experiment was performed in a complete randomized block design in three replicates. The following traits were determined: biomass (BIO), gross calorific value (GCV), basic density (BD), energy productivity (EP), energy density (ED), fixed carbon content (FCC), volatile material content (VMC) and ash content (AC) of different biomass components: wood, bark, branch and leaf. The effect of age significantly influenced all variables, providing an increasing distribution of BIO, EP, BD and ED. The four plant spacings provided different yields of BIO, EP, GCV and BD and the increased spacing caused a tendency to reduce BIO and EP values in all evaluated periods. In the 5th year, even being influenced by the spacing, the BD did not present a systematic increase or decrease over the provided living space. The three components of the trees induced a significant effect on the BIO, GCV, EP, FCC, VMC and AC variables.